1978
DOI: 10.3109/00365527809181748
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Investigation of Gastrin-producing Cells (G Cells)

Abstract: The mucosal distribution of G cells was quantitatively mapped in resected stomachs from 42 patients (12 with gastric ulcer, 11 with duodenal ulcer, 14 with duodenal ulcer and uremia, and 5 with gastric cancer). Along the histological border of the proximal part of the pyloric antrum there was in all patient categories a transitional zone of varying extent, with a low G-cell density before the cells disappeared in the body of the stomach. The proximal end of the duodenum contained considerably fewer G cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…Apart from this we failed to find gastrin cells within histologically normal fundal mucosa. This is in agreement with the findings of Stave andBrandtzaeg (1976) andHelmstaedter et al (1977). In the presence of pseudopyloric metaplasia within the fundus we consistently found small numbers of immunoreactive gastrin cells within the metaplastic mucosa.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Apart from this we failed to find gastrin cells within histologically normal fundal mucosa. This is in agreement with the findings of Stave andBrandtzaeg (1976) andHelmstaedter et al (1977). In the presence of pseudopyloric metaplasia within the fundus we consistently found small numbers of immunoreactive gastrin cells within the metaplastic mucosa.…”
Section: Discussionsupporting
confidence: 94%
“…This supports the findings of Asnaes et al (1976), who investigated antral mucosal biopsies and found an inverse correlation between gastrin cells and the degree of gastritis. Recently, While the above reports and the present study indicate reduced antial gastrin cells in gastritis, neither Meikle et al (1976) nor Fung et al (1977) X.4 Several authors have commented on the marked variation in gastrin cell concentration from one area of the stomach to another noted on studies on gastrectomy specimens (Delaney et al, 1978;Keuppens et al, 1978;Stave and Brandtzaeg, 1976). Similar var-ations have been reported in mucosal biopsies by Bussolati (1970), Creutzfeldt et al (1976), and Asnaes and Johansen (1975).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Nodular hyperplasia was diagnosed when nodular aggregates of at least five chromogranin-positive cells were seen. In the human stomach, gastrin cells are absent from the body mucosa (4,5), and gastrin immunostains were performed in 33 available cases to ensure that the biopsied tissue was from the body.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this study was undertaken to evaluate the diagnosis of AG on endoscopic biopsy specimens of body mucosa that still had oxyntic glands. We also employed immunostains for gastrin (a negative stain indicates that the biopsy specimen is truly from the body and not from the antrum or antral-oxyntic transitional zone (4,5)) and chromogranin to evaluate for ECL cell hyperplasia.…”
mentioning
confidence: 99%